Utilization of Mind Mapping to Increase Learning Creativity - Ayu Ismi Hanifah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
In the current learning process there are still many who use conventional methods or tend to be teacher-centered. This results in the inactivity of students which is feared will affect students' understanding which will have an impact on their learning outcomes. Therefore, the service took the initiative to provide training in order to increase the creativity of participants (in this case students) through the use of mind mapping. This service activity is expected to be applied to the process of learning activities so that there are interactions that occur in class. The service is carried out in three stages, including the preparation, implementation, and evaluation stages. At the evaluation stage, participants are given a questionnaire to assess the success of the activities that have been carried out. From the results of the dedication it was concluded that by utilizing this mind mapping it can foster creativity that can be poured by participants in a work.